Self-expanding intra-annular versus commercially available transcatheter heart valves in high and extreme risk patients with severe aortic stenosis (PORTICO IDE): a randomised, controlled, non-inferiority trial. Issue 10252 (5th September 2020) - Makkar, Raj R; Cheng, Wen; Waksman, Ron; Satler, Lowell F; Chakravarty, Tarun; Groh, Mark; Abernethy, William; Russo, Mark J; Heimansohn, David; Hermiller, James; Worthley, Stephen; Chehab, Bassem; et al.
Summary: Background: Randomised trial data assessing the safety and efficacy of the self-expanding intra-annular Portico transcatheter aortic valve system (Abbott Structural Heart, St Paul, MN, USA) compared with any commercially available valves are needed to compare performance among designs. Methods: In this prospective, multicentre, non-inferiority, randomised controlled trial (the Portico Re-sheathable Transcatheter Aortic Valve System US Investigational Device Exemption trial [PORTICO IDE]), high and extreme risk patients with severe symptomatic aortic stenosis were recruited from 52 medical centres experienced in performing transcatheter aortic valve replacement in the USA and Australia. Patients were eligible if they were aged 21 years or older, in New York Heart Association functional class II or higher, and had severe native aortic stenosis. Eligible patients were randomly assigned (1:1) using permuted block randomisation (block sizes of 2 and 4) and stratified by clinical investigational site, surgical risk cohort, and vascular access method, to transcatheter aortic valve replacement with the first generation Portico valve and delivery system or a commercially available valve (either an intra-annular balloon-expandable Edwards-SAPIEN, SAPIEN XT, or SAPIEN 3 valve [Edwards LifeSciences, Irvine, CA, USA]; or a supra-annular self-expanding CoreValve, Evolut-R, or Evolut-PRO valve [Medtronic, Minneapolis, MN, USA]). Investigational site staff, implanting physician, and study participant were unmasked to treatment assignment. Core laboratories and clinical event assessors were masked to treatment allocation. The primary safety endpoint was a composite of all-cause mortality, disabling stroke, life-threatening bleeding requiring transfusion, acute kidney injury requiring dialysis, or major vascular complication at 30 days. The primary efficacy endpoint was all-cause mortality or disabling stroke at 1 year. Clinical outcomes and valve performance were assessed up to 2 years after the procedure. Primary analyses were by intention to treat and the Kaplan-Meier method to estimate event rates. The non-inferiority margin was 8·5% for primary safety and 8·0% for primary efficacy endpoints. This study is registered with ClinicalTrials.gov, NCT02000115, and is ongoing. Findings: Between May 30 and Sept 12, 2014, and between Aug 21, 2015, and Oct 10, 2017, with recruitment paused for 11 months by the funder, we recruited 1034 patients, of whom 750 were eligible and randomly assigned to the Portico valve group (n=381) or commercially available valve group (n=369). Mean age was 83 years (SD 7) and 395 (52·7%) patients were female. For the primary safety endpoint at 30 days, the event rate was higher in the Portico valve group than in the commercial valve group (52 [13·8%] vs 35 [9·6%]; absolute difference 4·2, 95% CI −0·4 to 8·8 [upper confidence bound UCB 8·1%]; pnon-inferiority =0·034, psuperiority =0·071). At 1 year, the rates of the primary efficacy endpoint were similar between the groups (55 [14·8%] in the Portico group vs 48 [13·4%] in the commercial valve group; difference 1·5%, 95% CI −3·6 to 6·5 [UCB 5·7%]; pnon-inferiority =0·0058, psuperiority =0·50). At 2 years, rates of death (80 [22·3%] vs 70 [20·2%]; p=0·40) or disabling stroke (10 [3·1%] vs 16 [5·0%]; p=0·23) were similar between groups. Interpretation: The Portico valve was associated with similar rates of death or disabling stroke at 2 years compared with commercial valves, but was associated with higher rates of the primary composite safety endpoint including death at 30 days. The first-generation Portico valve and delivery system did not offer advantages over other commercially available valves. Funding: Abbott.